Flux-cored wire for 9% Ni steel welding

JP7638594B2Active Publication Date: 2025-03-04NIPPON STEEL WELDING & ENGINEERING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021051421
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-25
Publication Date
2025-03-04
Estimated Expiration
2041-03-25

AI Technical Summary

Benefits of technology

【0011】 本発明の9%Ni鋼溶接用フラックス入りワイヤによれば、9%Ni鋼の溶接において、全姿勢での溶接作業性に優れ、高強度で高靱性の溶接金属が得られ、かつ、ブローホール等の耐欠陥性に優れ、さらに耐割れ性に優れる等、高能率で高品質な溶接金属が得られる9%Ni鋼溶接用フラックス入りワイヤを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638594000006
    Figure 0007638594000006
  • Figure 0007638594000007
    Figure 0007638594000007
  • Figure 0007638594000001
    Figure 0007638594000001
Patent Text Reader

Abstract

To provide a flux-cored wire for welding 9% Ni steel that provides a weld metal with high strength and excellent toughness, and that is excellent in defect resistance and welding workability.SOLUTION: A flux-cored wire for welding 9% Ni steel in which a Ni-based alloy outer skin is filled with flux, contains Mn: 2.0 to 4.5%, Ni: 53 to 65%, Cr: 13 to 19%, Mo: 5 to 14%, W: 0.5 to 6%, Nb: 0.5 to 3.0%, Ti: 0.4 to 1.0%, Ta: 0.05 to 0.2%, with C: 0.04% or less, and Si: 0.2% or less by mass % in terms of the total mass of the wire in the total of the Ni-based alloy outer skin and the flux, and further contains TiO2 conversion value: 3.0 to 8.0%, SiO2 conversion value: 0.5 to 2.0%, ZrO2 conversion value: 1.0 to 2.0%, a total pf Na2O conversion value and K2O conversion value: 0.1 to 0.8%, CaO: 0.1 to 0.8%, F conversion value: 0.1 to 1.0% in the flux.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flux-cored wire for welding 9% Ni steel, which is used for welding 9% Ni steel that is mainly used for storage tanks for LNG (Liquefied Natural Gas) and the like, and relates to a flux-cored wire for welding 9% Ni steel that can obtain a weld metal with high strength and excellent toughness, has excellent resistance to cracking and defects such as blowholes, and is excellent in welding workability in all positions. [Background technology]

[0002] In recent years, in Japan, plans to expand LNG-fueled thermal power plants have been promoted, and LNG demand is expected to increase along with the expansion of city gas sales and the increase in usage due to industrial fuel conversion. Furthermore, LNG demand is also on the rise worldwide, and new construction and expansion of LNG storage tanks are being considered. These LNG storage tanks use 9% Ni steel as a ferritic cryogenic material, and have been mainly used as the inner tank material for LNG tanks.

[0003] On the other hand, for welding 9% Ni steel, the weld metal must have sufficient strength and excellent toughness at cryogenic temperatures, so Ni-based alloy welding materials are often used. In on-site welding of LNG tanks, welding of the inner tank side plate accounts for a large proportion of the overall construction process and cost, and traditionally, shielded metal arc welding or TIG welding has been mainly used for the vertical joints of the inner tank side plate, and submerged arc welding has been mainly used for the circumferential welds. However, welding of vertical joints using shielded metal arc welding or TIG welding has poor work efficiency, and there have been issues with reducing the burden of welding work and shortening the construction period.

[0004] Even for special materials such as Ni-based alloys, there is an increasing demand for gas-shielded arc welding using Ni-based alloy flux-cored wire, which is expected to improve the efficiency of welding work compared to covered metal arc welding and TIG welding. On the other hand, Ni-based alloys have a fully austenitic structure and are extremely susceptible to cracking. In addition, compared to carbon steel, Ni-based alloys have a low melting point and are prone to porosity defects such as blowholes, so there are issues with defect resistance. Furthermore, since tensile strength equivalent to that of steel plate and impact performance at extremely low temperatures are required, the weld metal is required to have both these properties and weldability, so the welding position and range of welding conditions are limited.

[0005] For example, Patent Document 1 proposes a flux-cored wire for 9% Ni steel welding, which has excellent defect resistance and specifies the C, Ti, Al, and Mg in the Ni-based sheath, contains Ni, Cr, Mo, Mn, W, Fe, Ti, and Mg in a specified range as the total mass of the wire, and suppresses C and Nb to a specified level or less. However, according to the technology disclosed in Patent Document 1, the Ti content in the total mass of the wire is low, and sufficient deoxidization effect cannot be obtained, so blowholes and the like are likely to occur, and there is a problem with defect resistance. In addition, the Nb content, which is a solid solution strengthening element, is low, and there are problems such as low strength of the weld metal in a fully austenitic structure such as a Ni-based alloy.

[0006] In addition, Patent Document 2 describes TiO sintered at 800°C or higher. 2 In the proposed technique, the powdered flux has a large surface area and is prone to reabsorb moisture after sintering. 2 There was also a problem of increased manufacturing costs due to the addition of additional steps such as firing the material.

[0007] Furthermore, Patent Document 3 specifies the amount of C in the Ni-based sheath and the total mass of the wire is TiO 2 or ZrO 2A flux-cored wire has been proposed that has good wire productivity defined by the above, excellent mechanical properties of the weld metal, and good welding workability in all positions. However, although the technology disclosed in Patent Document 3 achieves both the mechanical properties of the weld metal and the welding workability in all positions, there is room for improvement in crack resistance. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2015-85366 A [Patent Document 2] JP 2016-93836 A [Patent Document 3] JP 2018-144045 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been devised in view of the above-mentioned problems, and relates to a flux-cored wire for welding 9% Ni steel that is used for welding 9% Ni steel that is mainly used for storage tanks for LNG and the like, and has an object to provide a flux-cored wire for welding 9% Ni steel that can obtain a weld metal with high strength and excellent toughness, has excellent resistance to cracking and defects such as blowholes, and has excellent welding workability in all positions. [Means for solving the problem]

[0010] The gist of the present invention is a flux-cored wire for 9% Ni steel welding, which is made by filling a Ni-based alloy sheath with flux, and which contains, in mass % relative to the total mass of the wire, the total of the Ni-based alloy sheath and flux, Mn: 2.0 to 4.5%, Ni: 53 to 65%, Cr: 13 to 19%, Mo: 5 to 14%, W: 0.5 to 6%, Nb: 0.5 to 3.0%, Ti: 0.4 to 1.0%, Ta: 0.05 to 0.2%, C: 0.04% or less, and Si: 0.2% or less, and further contains, in mass % relative to the total mass of the wire, Ti oxide TiO 2Total of converted values: 3.0-8.0%, SiO of Si oxide 2 Total converted value: 0.5-2.0%, Zr oxide ZrO 2 Total of converted values: 1.0-2.0%, one or more of sodium oxide and potassium oxide: Na 2 O conversion value and K 2 The flux-cored wire for 9% Ni steel welding is characterized by containing 0.1-0.8% in total calculated as O, 0.1-0.8% in total calculated as CaO, 0.1-0.8% in total calculated as F of metal fluorides, and the remainder being Fe content of the Ni-based alloy sheath, Fe content of the iron alloy powder, and impurities. Effect of the Invention

[0011] According to the flux-cored wire for welding 9% Ni steel of the present invention, it is possible to provide a flux-cored wire for welding 9% Ni steel that is excellent in welding workability in all positions in welding 9% Ni steel, can provide a weld metal with high strength and high toughness, and can also provide a weld metal with excellent resistance to defects such as blowholes and further excellent cracking resistance, and can provide a high-quality weld metal with high efficiency. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a diagram showing the groove shape and lamination method of a welded joint whose defect resistance was evaluated. [Diagram 2] FIG. 13 is a diagram showing an example of evaluating arc stability by measuring voltage fluctuations. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In order to solve the above-mentioned problems, the present inventors have produced various flux-cored wires and have conducted detailed studies on the effects of the component compositions on the welding workability and mechanical properties.

[0014] As a result, by adjusting the amount of C, Ni, Cr, and Nb in the flux-cored wire, it was possible to obtain weld metal with excellent mechanical properties, but hot cracking occurred after welding. Therefore, further investigation was conducted into the composition of the components to prevent hot cracking while maintaining the mechanical properties of the weld metal. As a result, it was discovered that hot cracking occurs due to the segregation of impurity elements such as S and P, or the formation of low-melting point compounds such as Ni-Si and Ni-Nb. Therefore, it was discovered that by adjusting the amount of Mo, W, and Ta, which form compounds with relatively high melting points, it is possible to improve hot cracking resistance and obtain weld metal with good mechanical properties.

[0015] In addition, since the solidification temperature of Ni-based alloy weld metal is lower than that of carbon steel, the time to complete solidification is short, and there are problems such as CO gas being easily trapped inside the weld metal and easily generating porosity defects such as blowholes. Therefore, further investigation was conducted. As a result, it was found that adding an appropriate amount of Ti reduces the amount of oxygen in the weld metal, suppresses the CO reaction, and reduces blowholes. In addition, adding an appropriate amount of CaO adjusts the melting point and viscosity of the slag, suppresses the trapping of CO gas inside the slag and molten metal surface, reduces the occurrence of blowholes and pits, and produces weld metal with good defect resistance.

[0016] Furthermore, the welding workability is improved by the TiO 2 The sum of the converted values ​​of Si oxides, SiO 2 Sum of converted values, Al oxides 2 O 3 The sum of the converted values ​​of Zr oxides, ZrO 2 Total of converted values ​​and Na of CaO, Na oxide and K oxide 2 O conversion value and K 2 It has been found that by adjusting the total of one or more of the O-converted values ​​and the total of the F-converted values ​​of the metal fluorides to an appropriate amount, the arc state during welding, slag encapsulation, slag detachability, etc. can be improved.

[0017] The present invention has been made possible by the individual, coexistence, and synergistic effects of each component of the Ni-based alloy sheath and the filled flux, and the reasons for adding and limiting each component are described below. Note that the content of each component is shown in mass% relative to the total mass of the wire, and the description of mass% is simply written as %.

[0018] [Mn: 2.0~4.5% in total for Ni-based alloy sheath and flux] Mn is added to improve the cracking resistance of the weld metal. If the Mn content is less than 2.0%, the cracking resistance is deteriorated. On the other hand, if the Mn content exceeds 4.5%, the amount of spatter generation increases. Therefore, the total Mn content of the Ni-based alloy sheath and the flux is set to 2.0 to 4.5%. Note that Mn is not only contained in the Ni-based alloy sheath, but is also added from metallic Mn from the flux and alloy powder such as Fe-Mn.

[0019] [Ni-based alloy outer sheath and flux combined: 53-65% Ni] Ni is the main element that constitutes the weld metal, and is added to ensure strength and toughness at cryogenic temperatures by providing an austenitic structure. If Ni is less than 53%, the effect is not obtained, and the strength and toughness of the weld metal decrease. On the other hand, if Ni exceeds 65%, the toughness of the weld metal decreases. Therefore, the total Ni content of the Ni-based alloy sheath and flux is set to 53-65%. Note that Ni is not only contained in the Ni-based alloy sheath, but is also added from metallic Ni from the flux and alloy powder such as Fe-Ni.

[0020] [Ni-based alloy outer sheath and flux combined: Cr: 13-19%] Cr is added to ensure the strength and toughness of the weld metal. If the Cr content is less than 13%, the effect is not obtained, and the necessary strength and toughness of the weld metal cannot be obtained. On the other hand, if the Cr content exceeds 19%, the elongation of the weld metal decreases. Therefore, the total Cr content of the Ni-based alloy sheath and flux is set to 13-19%. Note that Cr is not only contained in the Ni-based alloy sheath, but is also added from metallic Cr from the flux and alloy powder such as Fe-Cr.

[0021] [Mo: 5-14% in total for Ni-based alloy sheath and flux] Mo is added to improve the strength of the weld metal and suppress hot cracking. If Mo is less than 5%, the effect is not fully obtained, and the strength of the weld metal decreases and hot cracking occurs. On the other hand, if Mo exceeds 14%, the toughness of the weld metal decreases. Therefore, the total Mo content of the Ni-based alloy sheath and flux is set to 5 to 14%. Note that Mo is not only contained in the Ni-based alloy sheath, but is also added from metallic Mo from the flux and alloy powder such as Fe-Mo.

[0022] [Ni-based alloy outer sheath and flux combined: W: 0.5-6%] W is added to suppress hot cracking. If W is less than 0.5%, the effect is not sufficient and hot cracking occurs. On the other hand, if W exceeds 6%, the tensile strength of the weld metal decreases. Therefore, the total W content of the Ni-based alloy sheath and flux is set to 0.5 to 6%. W is not only contained in the Ni-based alloy sheath, but is also added from metallic W powder from the flux.

[0023] [Ni-based alloy outer sheath and flux combined: 0.5-3.0% Nb] Nb is added to improve the strength of the weld metal. If the Nb content is less than 0.5%, the effect is not fully obtained, and the strength of the weld metal decreases. On the other hand, if the Nb content exceeds 3.0%, low melting point compounds such as Ni-Nb are generated, which makes hot cracks more likely to occur. Therefore, the total Nb content of the Ni-based alloy sheath and flux is set to 0.5 to 3.0%. Note that Nb is not only contained in the Ni-based alloy sheath, but is also added from alloy powder such as Fe-Nb from the flux.

[0024] [Ni-based alloy outer sheath and flux: Ti: 0.4-1.0%] Ti is added to reduce the amount of oxygen in the weld metal, inhibit CO reactions, reduce blowholes, and improve defect resistance. If Ti is less than 0.4%, the deoxidation reaction in the weld metal is insufficient, causing porosity defects such as blowholes. On the other hand, if Ti exceeds 1.0%, carbides precipitate and the elongation of the weld metal decreases. Therefore, Ti is set to 0.4 to 1.0%. Ti is contained in the Ni-based alloy sheath, and is also added from metallic Ti from the flux and alloy powder such as Fe-Ti.

[0025] [Ta: 0.05~0.2% in total for Ni-based alloy sheath and flux] Ta is added to suppress hot cracking. If the Ta content is less than 0.05%, the effect is not sufficient and hot cracking occurs. On the other hand, if the Ta content exceeds 0.2%, the toughness of the weld metal decreases. Therefore, the total W content of the Ni-based alloy sheath and flux is set to 0.05 to 0.2%. Ta is not only contained in the Ni-based alloy sheath, but is also added from metallic Ta powder from the flux.

[0026] [Ni-based alloy outer sheath and flux combined C: 0.04% or less] C has the effect of improving the strength of the weld metal, but if added in excess, it forms carbides and reduces toughness, so the content should be 0.04% or less. C is contained in the Ni-based alloy sheath, and is also added from the metal powder and alloy powder from the flux.

[0027] [Si: 0.2% or less in total for Ni-based alloy sheath and flux] Since silicon produces low melting point compounds such as Ni-Si and has the effect of promoting hot cracking, it is preferable to keep the content as low as possible. If the silicon content exceeds 0.2%, hot cracking will occur. Therefore, the total silicon content of the Ni-based alloy sheath and flux should be 0.2% or less. In addition to being contained in the Ni-based alloy sheath, silicon is also added from the metal powder and alloy powder from the flux.

[0028] [TiO in the flux] 2 Total conversion value: 3.0-8.0% Ti oxide is added to stabilize the droplet transfer and improve the arc stability. 2 If the total of the converted values ​​is less than 3.0%, the effect is not sufficient and the arc becomes unstable. 2 If the total of the converted values ​​exceeds 8.0%, the temper color will adhere to the bead surface and the bead appearance will be poor. Therefore, the TiO 2 The total converted value is 3.0 to 8.0%. Note that Ti oxide is added from powders such as rutile from flux, titanium oxide, titanium slag, and ilmenite.

[0029] [SiO of Si oxide in flux] 2 Total conversion value: 0.5-2.0% Silicon oxide is added to adjust the melting point of the slag and improve the appearance of the bead. 2 If the total of the converted values ​​is less than 0.5%, the effect is not sufficiently obtained, and the encapsulation of the slag becomes non-uniform, resulting in poor bead appearance. On the other hand, the SiO 2 If the total of the converted values ​​exceeds 2.0%, the melting point of the slag will be low, and it will be difficult for the molten slag generated during vertical upward welding to hold the molten metal, resulting in a convex bead shape. 2 The total converted value is 0.5 to 2.0%. Silicon oxide is added from powders such as silica sand, sodium silicate, and wollastonite from the flux.

[0030] [ZrO in flux 2 Total conversion value: 1.0~2.0% Zr oxide improves slag encapsulation and improves slag removability. ZrO 2 If the total of the converted values ​​is less than 1.0%, the effect is not sufficient, the encapsulation of the slag is non-uniform, and the slag removability is deteriorated. On the other hand, ZrO 2 If the total of the converted values ​​exceeds 2.0%, the viscosity of the slag increases, the droplet transfer is not smooth, and the amount of spatter increases. Therefore, ZrO 2The total converted value is 1.0 to 2.0%. Zr oxide is added from zircon sand from flux, zircon oxide powder, etc.

[0031] [One or more of sodium oxide and potassium oxide in the flux: Na 2 O conversion value and K 2 Total O equivalent value: 0.1-0.8% Na oxide and K oxide improve the melting point and viscosity of the slag and stabilize the arc. 2 O conversion value and K 2 If the total O-equivalent value is less than 0.1%, the effect is not sufficient and the arc becomes unstable. 2 O conversion value and K 2 If the total O equivalent value exceeds 0.8%, the droplets grow large, large spatters are generated, and the amount of spatter generated increases. Therefore, the presence of one or more of Na oxides and K oxides in the flux 2 O conversion value and K 2 The total of the O-equivalent value is 0.1 to 0.8%. Note that Na oxide and K oxide are added from the powder of potassium feldspar, sodium titanate, etc., and the solid water glass component made of sodium silicate and potassium silicate in the flux.

[0032] [CaO in flux: 0.1~0.8%] CaO adjusts the melting point and viscosity of the slag, inhibits the trapping of CO gas present in the slag and molten metal surface, reduces the occurrence of blowholes and pits, and improves defect resistance. If the CaO content is less than 0.1%, the effect is not fully obtained and blowholes and pits are more likely to occur. On the other hand, if the CaO content exceeds 0.8%, the droplet transfer is not stable and the arc becomes unstable. Therefore, the CaO content in the flux is set to 0.1 to 0.8%. CaO is added from powder such as wollastonite in the flux.

[0033] [Metal fluorides: 0.1-1.0% in total F conversion value] Metal fluorides are added to agitate the molten metal to prevent slag from being present in the weld metal. If the total F-equivalent value of the metal fluorides is less than 0.1%, the effect is not sufficient and slag becomes more likely to be present in the weld metal. On the other hand, if the total F-equivalent value of the metal fluorides exceeds 1.0%, the amount of spatter generated increases. Therefore, the total F-equivalent value of the metal fluorides in the flux is set to 0.1-1.0%. The metal fluorides are NaF, CaF 2 The F equivalent value is the total amount of F contained in these powders.

[0034] The balance of the flux-cored wire for 9% Ni steel welding of the present invention is the Fe content of the Ni-based alloy sheath, the Fe content of the iron alloy powder such as Fe-Mn, Fe-Ni, Fe-Cr, Fe-Mo, Fe-Nb, Fe-Ti, and impurities. There are no particular restrictions on the impurities, but from the viewpoint of hot cracking resistance, it is preferable that P is 0.010% or less and S is 0.010% or less.

[0035] In addition, if the flux filling rate in the Ni-based alloy sheath is less than 18%, the sheath becomes thick, the droplets become enlarged, and the arc becomes unstable. On the other hand, if the flux filling rate exceeds 30%, the sheath becomes thin, the amount of slag becomes excessive, and the slag encapsulation property deteriorates. Therefore, the flux filling rate is preferably 18 to 30%.

[0036] Regarding the manufacturing method of flux-cored wire, for example, when the outer sheath is formed into a tube shape from a steel strip, the flux is mixed, mixed, and dried and filled into a U-shaped groove, then formed into a round shape and drawn to the specified wire diameter. At this time, the shaped outer sheath seam can be welded to make a seamless flux-cored wire. When the outer sheath is a pipe, the pipe is vibrated to fill it with flux and the wire is drawn to the specified wire diameter.

[0037] In order to facilitate smooth supply and filling, the filling flux may be granulated with the addition of a binder (aqueous solution of potassium silicate and sodium silicate). EXAMPLES

[0038] Using the Ni-based alloy sheath shown in Table 1, flux-cored wires for welding 9% Ni steel were produced with various compositions shown in Table 2. The wire diameter was 1.2 mm, and the flux filling rate was 18 to 25%.

[0039] [Table 1]

[0040] [Table 2]

[0041] Using these prototype flux-cored wires, the deposited metal performance, defect resistance, crack resistance and welding workability were investigated.

[0042] The mechanical properties were evaluated by tensile tests and impact tests in accordance with JIS Z 3335. Welding was performed under the welding conditions No. 1 shown in Table 3. In the tensile test, a tensile strength of 690 MPa or more and an elongation of 27% or more were considered good, and in the impact test, an absorbed energy of 55 J or more on average for three pieces at a test temperature of -196°C was considered good.

[0043] [Table 3]

[0044] For the defect resistance investigation, steel plate symbol A1 shown in Table 4 was used. For welding, a 12 mm thick steel plate 1, a 60° V groove, a root gap of 4 mm, and a groove with a 4 mm thick backing metal 2 as shown in Figure 1 were welded under welding condition No. 1 shown in Table 3. For evaluation, an X-ray transmission test was performed in accordance with JIS Z 3106, and classification based on the number of flaws, Class 2 or less, was deemed good, and Class 3 or more, poor.

[0045] [Table 4]

[0046] The crack resistance was investigated using steel plate A2 shown in Table 4, in accordance with JIS Z 3153, and welding was performed under condition No. 1 shown in Table 3. The crack resistance was evaluated by investigating the presence or absence of cracks in the weld bead, excluding the crater.

[0047] For the evaluation of welding workability, steel plate A1 shown in Table 4 was used, and horizontal fillet welding and vertical upward welding were performed under welding conditions No. 1 and No. 2 shown in Table 3, and the arc stability, amount of spatter generation, slag removability, bead appearance, and bead shape were investigated.

[0048] The stability of the arc was evaluated based on the magnitude of the voltage fluctuation measured for 10 seconds during horizontal fillet welding. The evaluation is shown in the time-series voltage fluctuation chart in Figure 2. When the threshold value is set to ±1V from the average voltage, as shown in Figure 2(a), the voltage fluctuation is within the threshold. Exceed Time is 10 seconds 10 %, the arc was deemed stable, and as shown in Figure 2(b), the arc was deemed unstable when the time during which the voltage fluctuation exceeded the threshold exceeded 10% for 10 seconds.

[0049] The amount of spatter generated was measured using a copper collection box during horizontal fillet welding for 1 minute, and the value per unit time (g / nin) was obtained. A spatter generation rate of 1g / min or less was considered good. The results are summarized in Table 5.

[0050] After welding, the solidified slag on the surface of the weld bead was struck with a chipping hammer (total length 300 mm, weight 350 g) by lightly swinging it down in an arc around the handle. If the slag cracked and could then be easily removed with a brush, the result was rated as good; if the slag adhered to the bead surface and could not be removed, the result was rated as poor.

[0051] The bead appearance and shape were evaluated as good if there were no undercuts or overlaps that required reworking in the healthy weld bead. The bead appearance was evaluated as good if there was no partial disturbance in the waveform and it was uniform.

[0052] [Table 5]

[0053] In Tables 2 and 5, Wire Nos. 1 to 15 are examples of the present invention, and Wire Nos. 16 to 30 are comparative examples. Wire Nos. 1 to 15, which are examples of the present invention, contain Mn, Ni, Cr, Mo, W, Nb, Ti, Ta, C, Si, Ti oxide TiO 2 The sum of the converted values ​​of Si oxides, SiO 2 The sum of the converted values ​​of Zr oxides, ZrO 2 Sum of converted values, Na oxide and K oxide type 1 or type 2 Na 2 O conversion value and K 2 Since the total of the O equivalent value and the total of the F equivalent values ​​of CaO and metal fluorides were appropriate, the tensile strength, elongation and absorbed energy of the deposited metal were high, the classification based on the number of flaws in the X-ray transmission test was good (class 2 or less), and no cracks were found in the cracking test. In the welding workability test, the arc was stable, the amount of spatter generation was small, the slag removability was good, and the bead appearance and bead shape were also good, resulting in extremely satisfactory results.

[0054] In the comparative example, wire No. 16 had a low Mn content, so cracks occurred in the cracking test, and because it had a high Ta content, the absorbed energy of the deposited metal was low.

[0055] Wire No. 17 had a large amount of Mn, so it generated a large amount of spatter. Also, it had a large amount of C, so the absorbed energy of the deposited metal was low.

[0056] Wire No. 18 had a low Ni content, so the tensile strength and absorbed energy of the deposited metal were low. Also, because it had a high Si content, cracks occurred in the cracking test.

[0057] Wire No. 19 has a high Ni content, so the absorbed energy of the deposited metal was low. Also, the Ti oxide TiO 2 Because the converted value was small, the arc was unstable.

[0058] Wire No. 20 had a low Cr content, so the tensile strength and absorbed energy of the deposited metal were low. In addition, the SiO 2 Since the total converted value was small, the slag coverage was non-uniform and the bead appearance was poor.

[0059] Wire No. 21 had a high Cr content, so the elongation of the deposited metal was low. Also, the SiO 2 Since there were many of them, vertical upward welding was used to create a convex bead.

[0060] Wire No. 22 had a low Mo content, so the tensile strength of the deposited metal was low. Also, because of the low Mo content, cracks occurred in the cracking test. Furthermore, the Zr oxide ZrO 2 Since the amount of slag was small, the slag coverage was non-uniform and the slag removability was poor.

[0061] Wire No. 23 has a high Mo content, so the absorbed energy of the deposited metal was low. Also, the Zr oxide ZrO 2 Since the total converted value was large, a large amount of spatter was generated.

[0062] Wire No. 24 is W Because there are few In the cracking test, cracks occurred. 、 Na oxide and K oxide 2 O conversion value and K 2 The total O conversion value was small, so the arc was unstable.

[0063] Wire No. 25 had a high W content, so the tensile strength of the weld metal was low. In addition, the Na oxide and K oxide Na 2 O conversion value and K 2 The total O equivalent value was high, so there was a lot of spatter generation.

[0064] Wire No. 26 had a low Nb content, so the tensile strength of the deposited metal was low. Also, because it had a low CaO content, there were many blowholes in the X-ray examination, and it was classified as poor based on the number of defects.

[0065] Wire No. 27 had a high Nb content, so it cracked in the cracking test. Also, because the total F-converted value of metal fluorides was low, no slag inclusion occurred in the X-ray examination, and it was classified as defective with a high score.

[0066] Wire No. 28 had a low Ti content, so it had many blowholes in the X-ray examination and was classified as poor based on the number of defects. Also, it had a high CaO content, so the arc was unstable.

[0067] Wire No. 29 had a low elongation of the deposited metal due to its high Ti content, and a large amount of spatter was generated due to its high total F-converted value of metal fluorides.

[0068] Wire No. 30 had a small amount of Ta, so it cracked in the cracking test. Also, Ti oxide TiO 2 Because the conversion value was high, the temper color adhered to the bead surface, resulting in poor bead appearance. [Explanation of symbols]

[0069] 1 steel plate 2 Backing

Claims

[Claim 1] In a 9% Ni steel welding flux-cored wire having a Ni-based alloy sheath filled with flux, The total mass of the Ni-based alloy sheath and flux is expressed as a percentage by mass of the total mass of the wire. Mn: 2.0 to 4.5%, Ni: 53-65%, Cr: 13-19%, Mo: 5 to 14%, W: 0.5 to 6%, Nb: 0.5-3.0%, Ti: 0.4-1.0%, Ta: 0.05 to 0.2%; C: 0.04% or less, Si: 0.2% or less; Furthermore, in the flux, the mass percentage relative to the total mass of the wire is: Ti oxide TiO 2 Total conversion value: 3.0-8.0%, Silicon oxide SiO 2 Total conversion value: 0.5-2.0%, Zr oxide ZrO 2 Total conversion value: 1.0-2.0%, One or more of Na oxide and K oxide: Na 2 O conversion value and K 2 Total O equivalent value: 0.1 to 0.8% CaO: 0.1-0.8%, Metal fluorides: Contains 0.1 to 1.0% in total in terms of F; The remainder of the flux-cored wire for welding 9% Ni steel is the Fe content of the Ni-based alloy sheath, the Fe content of the iron alloy powder, and impurities.

Citation Information

Patent Citations

  • Flux cored wire for gas protection electrical arc welding

    CN1966199A

  • Flux cored wire for 9% ni steel

    JP1996309583A

  • Flux cored wire for welding 9% nickel steel

    JP1998296486A

  • Nickel base alloy flux-cored wire excellent in weldability at whole posture

    JP2000343277A

  • Ni-GROUP ALLOY FLUX-CORED WIRE

    JP2015085366A